2019
DOI: 10.1055/a-0927-7041
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS- and NMR-Guided Isolation of Monoterpene Dimers from Cultivated Thymus vulgaris Varico 3 Hybrid and Their Antityrosinase Activity

Abstract: Targeted isolation based on a combination of NMR and HPLC-PDA-MS of a dichloromethane extract of Thymus vulgaris Varico 3 aerial parts afforded one new p-cymene dimer, 6,3′,4′-trihydroxy-5,5′-diisopropyl-2,2′-dimethylbiphenyl (1), together with two known p-cymene derivatives (2 and 3), as well as five known compounds, namely, thymol (4), oleanolic acid (5), ursolic acid (6), cirsimaritin (7), and xanthomicrol (8). The structural elucidation of all compounds was performed by spectroscopic analyses, including 1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Ten µL of compound was dissolved in DMSO (final concentration 100 µM) and incubated with 40 µL mushroom tyrosinase (5370 U/mg–1 mg/2.6 mL buffer) and 200 µL of L-Dopa (1.5 mM) in 0.1 M Na-phosphate buffer (pH = 6.5) for 20 min at 37 °C. Then the enzyme reaction was monitored by measuring the change in absorbance at 490 nm due to the formation of the DOPA-chrome and compared with the standard inhibitor kojic acid [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ten µL of compound was dissolved in DMSO (final concentration 100 µM) and incubated with 40 µL mushroom tyrosinase (5370 U/mg–1 mg/2.6 mL buffer) and 200 µL of L-Dopa (1.5 mM) in 0.1 M Na-phosphate buffer (pH = 6.5) for 20 min at 37 °C. Then the enzyme reaction was monitored by measuring the change in absorbance at 490 nm due to the formation of the DOPA-chrome and compared with the standard inhibitor kojic acid [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies were conducted on the enzyme inhibitory properties of basil, thyme, and oregano EOs or extracts. The literature indicates that these species had significant potential as natural enzyme inhibitors as well as antioxidants [64][65][66][67][68][69][70][71]. Furthermore, our findings shed light on the valuable activity of post-distillation by-products, which can be used to develop novel enzyme inhibition drugs.…”
Section: Enzyme Inhibitory Activity Of Essential Oils Total Spent And...mentioning
confidence: 64%
“…demonstrated significant anti-tyrosinase activity ( Kim et al, 2021 ). In another study, again phytochemicals isolated from T. vulgaris L. such as 6′,3′,4′-trihydroxy-5,5′-diisopropyl-2,2′-dimethylbiphenyl, thymol, oleanolic acid, ursolic acid, cirsimaritin, and xanthomicrol were capable of inhibiting tyrosinase, which also proves only specific compounds are responsible for the tyrosinase inhibitory activity and this activity is only expected when they are present in the extracts ( Stefanis et al, 2019 ). The same conclusion is also accurate for the anti-urease activity and reported by Boga et al (2021a) ’s study again, no tyrosinase urease activity was demonstrated by the investigated ten Thymus L .…”
Section: Resultsmentioning
confidence: 94%